Electrospinning Material, Techniques, and Biomedical Applications - Haider, Sajjad; Haider, Adnan (IntechOpen, 2016)
This is a timely, an informative, an interesting, and a well-managed book. The book not only offers an in-depth review of the current status of the knowledge of electrospinning and its biomedical applications but also discusses the emerging ideas and features, both from the East and West, with a focus on the needless electrospinning for the production of uniform fibers. The book is equally helpful to the experts of this field, who wish to enhance their understanding of the emerging technologies, and to the new comers, who can use this book as a reference.